Educational Ideal of Ukrainian Ethnopedagogies: Carpathian Vector - Lysenko, Nelly (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
Educational ideal, methods, forms and means of folk-educational influence on its formation, starting from the first years of baby’s life are topical problems for researchers. The main element is an aim. The aim is an ideal image of the expecting result which is regarded as a guide for the educational activity of a certain ethnic community. The content of the notion of educational ideal is the imagery about the most important qualities of a personality, their manners, culture of relationship in the society, behavior. Ukrainian mentality is practicality, rationality, generosity, intellect in general. It is fully reflected in the pedagogical aim. At the same time mental means spiritual. That is something in thoughts and intents of a person. It is important to emphasize that Ukrainian ethos was formed on the basis of several groups, not only having formed a nation, but also having synthesized the temperament, traditions and customs, clothes and everyday life, culture in general. Hutsul, Boyko, Lemko (121 ethnic groups all together) differ by the uniqueness of the appearance. At the same time their internal essence, that is educational ideal, world view, ethic morals, are unchangeable. Educational ideal is historically determined. Esthetic strategies, formation of creativity, development of the abilities by the means of folk crafts and trades, upbringing of a host pierce through the educational ideal of nowadays Ukrainians. The people aim to bring up their children as true citizens: good kids mean quiet old age, while with evil children old age becomes a hell. Thus, the educational ideal of the Ukrainians should be considered as a basis for modern educational technologies projection.